GOOD CORPORATE GOVERNANCE AS MODERATING INFLUENCE OF FREE CASH FLOW ON THE PRACTICE INCOME MINIMIZATION - Wicaksana, Putu Krisnanda Ari (E-Jurnal Akuntansi, 2017)
The purpose of this study was to investigate the influence of free cash flow on income minimization as well as to determine whether moderate GCG (weaken) the effect of free cash flow on income minimization. The study was conducted on companies listed on the Indonesian Stock Exchange (BEI) 2011-2015. Sample selection technique used is purposive sampling. The data collection is done by the method of documentation and analysis techniques used are simple regression test and Moderated Regression Analysis (MRA). Based on the research with 28 companies, it is known that free cash flow negative effect on the income minimization. These results prove that the higher the amount of free cash flow, the income minimization practices will be smaller. The study also found that GCG able to moderate the influence of free cash flow on income minimization. It proves that with higher corporate governance in a company, then the influence of free cash flow on income minimization will wane.
Keywords: earnings management, income minimization, free cash flow, good corporate governance